Clementine explores the Moon - Spudis, Paul D.; Bussey, Ben; orcid:0000-0003-3391-0417 (Lunar and Planetary Institute, 1997)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University A selection of imagery and global data coverage obtained by the Clementine spacecraft. compiled by Paul D. Spudis and D. Ben J. Bussey. Clementine Spacecraft--Launch: January 25, 1994--Image Types--Dark-Halo Crater on the Floor of Schrödinger Basin--Nearside Albedo--Farside Albedo--Tycho Mosaics--Copernicus Color--Copernicus Color and Topography--Aristarchus Plateau (Real Color)--Aristarchus Plateau (False Color)--Aristarchus Plateau (Iron Map)--Apollo 16 Site (Metric Photo View)--Apollo 16 Site (Real Color)--Apollo 16 Site (False-Color Composite)--Apollo 16 Site (Map of Iron Concentration)--Global Iron Data--Global Titanium Data--Global Topography--Global Crustal Thickness--Full-Resolution Mosaic of Orientale Basin--Color Units of the Orientale Basin--Iron Concentrations of the Orientale Basin--Orientale Topography (Basin-Centered)--South Pole-Aitken Basin--South Pole-Aitken Basin-Centered Maps--Dionysius (Real Color)--Dionysius (Iron Map)--South Pole Mosaic--North Pole Mosaic--South Pole Mosaics (First and Second Month Lunar Mapping)--Polar Composites (Darkness/Illumination Maps)--Star Tracker Image--Earthrise--Full Earth Mosaic. Second edition